Functional Deimmunization of Interferon Beta-1b by Identifying and Silencing Human T Cells Epitopes - Amin Moradi Hasan-Abad; Elham Adabi; Esmaeil Sadroddiny; Mohammad Reza Khorramizadeh; Mohammad Ali Mazlomi; Saeed Mehravar; Gholam Ali Kardar (Iranian Journal of Allergy, Asthma and Immunology, 2019)
Interferonbeta-1b (IFNβ-1b) developed as therapeutic protein for the treatment of multiple sclerosis (MS). Studies have been shown that Long-term usage of this protein can lead to the development of anti-drug antibodies (ADAs) and this phenomenon cause total loss or reduced efficacy of IFNβ-1b. The aim of this study was to predict and silence IFNβ-1b T-cells epitopes by in silico methods and genetic engineering. Based on bioinformatics studies we identified optimal sets of conservative point mutations for eliminating T-cells epitopes in IFNβ-1b protein. Four synthetic genes with desirable mutation constructed and PET26b+ was used as an expression vector in E. coli. The expression of this proteins confirmed by SDS-PAGE and Western blotting, consequently, IFNβ-1b proteins was purified by His-tag chromatography. To determined activity of mutants’ variants anti-proliferative and anti-viral activity compared to wild form was evaluated using MTT assay in A549 and Vero cells lines respectively. Also the immunogenicity of mutant proteins compared with Betaseron measured in BALB/c mice. The in vitro bioactivity analysis demonstrated that functional activities of all mutant proteins were maintained and is the same as biological activity of Betaseron. Pharmacokinetic studies suggest that, in engineered proteins that contain substitution of Histidine to Glutamic Acid at position 131 (mut 2 and mut 1+2) antibodies response reduced by about 50%, as compared to that for Betaseron. Computational analysis expedites identification and prediction of epitopes in therapeutic protein, therefore, we used immunoinformatic tools for modification of dominant T-cell epitope in IFNβ-1b protein, and this strategy has capacity to create proteins which have naturally reduced immunogenicity.